Distinguishing Meningioma From Metastasis of Prostate Cancer on 68Ga-PSMA PET/CT. (November 2021) - Filizoglu, Nuh; Oksuzoglu, Kevser; Ozguven, Salih
Abstract : Abstract: Meningiomas are typically benign and the most common primary brain tumors. They are usually diagnosed based on their characteristic appearance on both MRI and CT. Meningiomas can easily be misdiagnosed as metastasis of prostate cancer due to their high 68 Ga-PSMA uptake on 68 Ga-PSMA PET/CT. We present a case of a metastatic prostate adenocarcinoma with PSMA-avid lesion in the right frontal lobe on 68 Ga-PSMA PET/CT. Later, MRI confirmed the brain lesion as meningioma.